2019
DOI: 10.2147/ott.s186806
|View full text |Cite
|
Sign up to set email alerts
|

<p>SMYD2-OE promotes oxaliplatin resistance in colon cancer through MDR1/P-glycoprotein via MEK/ERK/AP1 pathway</p>

Abstract: Background: SET and MYND domain-containing protein 2 (SMYD2-OE) plays an important role in cancer development through methylating histone and non-histone proteins. However, little is known about the relevance of SMYD2-OE in colon cancer. Moreover, oxaliplatin (L-OHP) is applied as first line for colon cancer chemotherapy, but drug resistance restricts its efficacy. Unexpectedly, the mechanism of L-OHP resistance in colon cancer remains unclear. In this study, we investigated the relationship of SMYD2-OE expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 33 publications
2
14
0
Order By: Relevance
“…Accumulating evidence has indicated that SMYD2 is associated with the drug resistance in several cancers, including non-small cell lung cancer, renal cell carcinoma and colon cancer (Ren et al, 2019;Shang and Wei, 2019;Yan et al, 2019). Our results showed that the inhibition of SMYD2 could significantly increase the sensitivity of chemo drugs in glioma cells.…”
Section: Discussionsupporting
confidence: 52%
“…Accumulating evidence has indicated that SMYD2 is associated with the drug resistance in several cancers, including non-small cell lung cancer, renal cell carcinoma and colon cancer (Ren et al, 2019;Shang and Wei, 2019;Yan et al, 2019). Our results showed that the inhibition of SMYD2 could significantly increase the sensitivity of chemo drugs in glioma cells.…”
Section: Discussionsupporting
confidence: 52%
“…SMYD2 was identified as a methyltransferase that methylates several key cancer-involved proteins, including retinoblastoma, p53, MAPKAPK3, and STAT3, to promote cancer development [ 5 , 8 , 21 , 32 ]. SMYD2-regulated cell proliferation is amongst these mechanisms that was reported in various types of cancers, for instance, colon cancer [ 9 , 35 ]. However, a recent study using small molecule inhibitors and CRISPR/Cas9 technology targeting SMYD2 in hundreds cancer cell lines questioned the functional role of SMYD2 in tumor cell proliferation [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The PMT SMYD2 12 , 14 , 30 , as an oncogene, is closely connected with transcriptional regulation, epigenetics, and tumorigenesis 31 , 32 . SMYD2 is highly expressed and related to poor prognosis in multiple cancers, including BC 11 , esophageal squamous cell carcinoma 10 , acute lymphoblastic leukemia 12 , gastric cancer 9 , hepatocellular carcinoma 33 , and colon cancer 34 . In our study, we found that SMYD2 expression was upregulated in sample datasets procured from online databases, as well as in LUAD cell lines and tissues.…”
Section: Discussionmentioning
confidence: 99%